2023
DOI: 10.1007/s13384-022-00577-6
|View full text |Cite
|
Sign up to set email alerts
|

‘Teachers are the guinea pigs’: teacher perspectives on a sudden reopening of schools during the COVID-19 pandemic

Abstract: Primary and secondary education systems experienced substantial disruption during the COVID-19 pandemic. However, little is known about how public health policy has affected Australian teachers during the pandemic. This study examines teacher perspectives on a sudden change of policy, whereby schools were abruptly opened to students at the beginning of the pandemic. At the same time, strict social distancing rules applied to the remainder of the population. Qualitative data from 372 Western Australian schoolte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…Indeed, participants voiced an ongoing experience of this throughout COVID-19 that they had interpreted as continued disrespect from the government for the teaching profession. Similar to our study findings, these negative sentiments were evident in teachers in other countries during COVID-19, including teachers in Australia who reported that sudden shifts in school opening decisions signified the government's disrespect for the profession and analogised themselves as being treated like guinea pigs, scapegoats and babysitters (Ryan et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, participants voiced an ongoing experience of this throughout COVID-19 that they had interpreted as continued disrespect from the government for the teaching profession. Similar to our study findings, these negative sentiments were evident in teachers in other countries during COVID-19, including teachers in Australia who reported that sudden shifts in school opening decisions signified the government's disrespect for the profession and analogised themselves as being treated like guinea pigs, scapegoats and babysitters (Ryan et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
“…The teaching profession was no exception, with teachers around the world reporting how they were negatively portrayed and perceived as a profession (e.g. Nerlino, 2023; Ryan et al, 2023). The importance of valuing the teaching profession has been recognised at the international level, including by the OECD (Schleicher, 2018) and Education International (Stromquist, 2018), as it is associated with the teacher recruitment and retention crisis.…”
Section: Discussionmentioning
confidence: 99%
“…After being closed since March 2020, institutes of higher education in India reopened for academic activities in physical mode in the second week of February 2022. Contrary to the expectation of normalization and reduction in the negative impact caused by COVID-19, teachers initially showed fear of contamination, other health-related concerns, and family-and work-related concerns in different parts of the world (Wakui et al, 2021;Ryan et al, 2023). A qualitative survey of Australian teachers (Ryan et al, 2023) reported increased workload and diminished wellbeing.…”
Section: Introductionmentioning
confidence: 91%
“…The global COVID-19 pandemic is considered a mass traumatic event that has drastically altered people's working conditions and had a negative impact on workers' health [1,2]. The COVID-19 crisis forced teachers across the world and in Israel to switch to online or hybrid teaching [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Upon the reopening of the schools, teachers faced a new reality and challenging routines characterized by social distancing in the classroom, alternative teaching approaches to reduce learning gaps, online team meetings, new hygiene measures and hybrid teaching [6,7]. Most studies that examined teachers' emotional well-being during the pandemic focused primarily on negative aspects [2,8,9]. Indeed, following the COVID-19 pandemic, the new teaching requirements and the high expectations of themselves were a source of anxiety and stress [8].…”
Section: Introductionmentioning
confidence: 99%